Komunikasi Interpersonal dalam Pendampingan Pemanfaatan Digitalisasi Keuangan UMKM di Kelurahan Abadijaya Depok - Salman, Dhani; Faturahman, Muhammad Ilham Aji; Astika, Yuly; Widyawan, Bisma (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The digital transformation in the MSME sector is inevitable and requiresnot only technological readiness but also adaptive and humanizedcommunication approaches. This study aims to understand howinterpersonal communication influences the success of financialdigitalization assistance for MSMEs through the SIAPIK application inAbadijaya Sub-district, Depok. Using a descriptive qualitative approach,data were collected through in-depth interviews, participatoryobservation, and Likert-scale questionnaires. Findings indicate thatclarity of communication, empathetic attitude of facilitators, and theability to adjust communication styles are crucial to the successfuladoption of digital applications. Interpersonal communication plays afundamental role in bridging technological resistance and building trust inlearning processes. This study emphasizes the importance of relationaldimensions in MSME digitalization strategies and recommendsstrengthening interpersonal communication skills in community-basedassistance programs.